LOGISTICS OF MACHINERY AND EQUIPMENT REPAIR PROCESSES IN THE MANUFACTURING INDUSTRY - Grondys, Katarzyna; Kott, Iga; Wójcik-Mazur, Agnieszka (Advanced Logistic Systems - Theory and Practice, 2016)
Maintaining continuity of production is an extremely important factor in the functioning of entities in the manufacturing industry. The importance of machinery and equipment maintenance is growing in the area of carrying out planned and emergency repairs to ensure the availability of spare parts or implementation of systematic maintenance. The article includes a logistic model of the process of repair and includes indicators of inventory management of spare parts. Simultaneous necessity to reduce production costs and efficient management of replacement parts logistics requires further actions and the use of new tools. The aim of the paper has been to present the selected indicators of the repair process and the availability of facilities, taking into account their critical features affecting the organization of this process. There have also been presented the main components of the process of eliminating damage based on the model of logistics repair. As a result of the conducted analyses, there have been identified the most important aspects of management of the repair process in the production company.